2022
DOI: 10.3233/bpl-220140
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Dietary Factors Mediate Neural Plasticity Through Modulation of BDNF Signaling

Abstract: The term “neural plasticity” was first used to describe non-pathological changes in neuronal structure. Today, it is generally accepted that the brain is a dynamic system whose morphology and function is influenced by a variety of factors including stress, diet, and exercise. Neural plasticity involves learning and memory, the synthesis of new neurons, the repair of damaged connections, and several other compensatory mechanisms. It is altered in neurodegenerative disorders and following damage to the central o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Çalışmamızın amacı, son yıllarda hem sağlıklı hem de hastalıklı popülasyonlarda egzersize bağlı BDNF seviyelerini inceleyen çeşitli araştırmalar ışığında (23)(24)(25), haftada 20 saat yoğun antrenman yapan Türk milli judo takımı ile hareketsiz bireyler arasındaki bazal BDNF seviyelerini karşılaştırmaktır.…”
Section: Discussionunclassified
“…Çalışmamızın amacı, son yıllarda hem sağlıklı hem de hastalıklı popülasyonlarda egzersize bağlı BDNF seviyelerini inceleyen çeşitli araştırmalar ışığında (23)(24)(25), haftada 20 saat yoğun antrenman yapan Türk milli judo takımı ile hareketsiz bireyler arasındaki bazal BDNF seviyelerini karşılaştırmaktır.…”
Section: Discussionunclassified
“…It has been demonstrated that crosstalk between the periphery and the brain can be triggered by exercise resulting from the release of molecules and factors from the liver, muscles, and bones into the bloodstream to support neuronal plasticity ( Stephan & Sleiman, 2021 ) ( Figure 1 ). These exercise-induced factors activate convergent neural pathways, with BDNF signaling in the central role of this coordinated response ( Fakhoury et al, 2022 ). Upon exercise, the muscle secretes several factors that activate BDNF signaling and regulate neural plasticity such as the myokine fibronectin type III domain-containing protein 5 (FNDC5) ( Wrann et al, 2013 ), and lactate ( El Hayek et al, 2019 ).…”
Section: Physical Exercise In Alleviating Symptoms Of Major Depressionmentioning
confidence: 99%
“…Unfortunately, dysbiosis negatively affects mucin Health, sport, rehabilitation Health, sport, rehabilitation Здоров'я, спорт, реабілітація Здоров'я, спорт, реабілітація Здоровье, спорт, реабилитация Здоровье, спорт, реабилитация 2023 9(4) 100 production and intestinal peristalsis and influences depression by affecting hypothalamic-pituitaryadrenal axis and modulating neurotransmitters synthesis such as brain-derived neurotrophic factor (BDNF) and serotonin [62,63]. The BDNF can play a role in neuroprotection, neuroplasticity, and neuronal activity [64]. Additionally, oxidative stress is associated with decreasing intestinal tight junction proteins such as Claudin (CLDN) and Zonula occludens (ZO-1), inducing lipopolysaccharides (LPS) translocation and increasing cytokines production, mainly tumor necrosis factors-α (TNF-α), TNF-β, and interleukin-6 (IL-6) in IBS patients [65].…”
Section: Do Physical Exercises Impact Irritable Bowel Syndrome and How?mentioning
confidence: 99%